Dedikasi Melalui Kebugaran Jasmani Terhadap ABK Di SLB PRI Buaran Pekalongan - Imroatul Maghfiroh, Imroatul (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail, 2022)
The purpose of this community service is dedication through physical fitness exercises that can be done every day for Children with Special Needs so that their physical fitness is well maintained. This community service was carried out at SLB PRI Buaran Pekalongan. The material presented at this seminar is about forms of physical fitness exercise that can be done every day for Children with Special Needs. The results of the implementation of community service are expected to give the spirit of Children with Special Needs where physical fitness must be maintained every day.